Notas sobre el documental peruano contemporáneo - Varotto, Viola (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
This article is a summary of the current situation on the Peruvian contemporary documentary and an analysis of the forms of audiovisual language management, the promotion of production, as well the training spaces. It proposes, as a reminder, some contemporary filmmakers whose works have been recognized in the local and international media. Finally, it delineates the profile of the contemporary filmmaker.

El presente artículo es un resumen de la situación actual sobre el documental contemporáneo peruano y un análisis de las formas de manejo del lenguaje audiovisual, el fomento a la producción, así como de los espacios de formación. Propone, a manera de recordatorio, algunos realizadores contemporáneos cuyos trabajos han sido reconocidos en el medio local e internacional. Finalmente, delinea el perfil del cineasta contemporáneo.
Notes about contemporary peruvian documentary
Keywords: Documental; Arte contemporáneo; Cine; Industria cultural; Vanguardia; Lenguaje Audiovisual; https://purl.org/pe-repo/ocde/ford#5.09.01